Numb chin syndrome: A case series of a clinical syndrome associated with malignancy. Issue 6 (26th June 2014) - Tejani, Neetu; Cooper, Adam; Rezo, Angela; Pranavan, Gane; Yip, Desmond
Abstract Introduction Information regarding the appropriate work‐up and outcomes in patients receiving palliative treatment for numb chin syndrome (NCS) in the setting of malignancy is sparse. This study aims to describe NCS in malignancy and evaluate the disease trajectory, significance of diagnostic modalities and outcomes with palliative treatment. Methods A retrospective study was performed on patients presenting with NCS between March 2007 and October 2013 at the Capital Region Cancer Service, Canberra. Results Thirteen patients were identified who presented with numbness of the chin between March 2007 and October 2013. Seven patients had breast cancer, two had prostate cancer, two had multiple myeloma, one had medulloblastoma and one had an adenoid cystic salivary gland tumour. The mean interval from initial cancer diagnosis to development of the syndrome was 4.32 years. Twelve out of 13 patients had had prior chemotherapy with two or more lines of treatment (with a median of two lines), indicating this condition tended to present late in the course of disease in our patients. Four patients developed bilateral symptoms, and in two of these cases the metastatic lesion was in the base of the skull. Eleven out of 13 patients had positive signs on imaging. Nine out of 13 patients received palliative radiotherapy, with clinical response in eight patients. Conclusion Patients with malignancy presented with NCS late in the disease trajectory, often after multiple lines of treatment. In our cohort of patients, 84% had positive imaging signs to aid diagnosis, and 77% had resolution of numbness with palliative treatment.